Effects of weight stigma in news media on physical activity, dietary and weight loss intentions and behaviour - Lambert, ER; Koutoukidis, DA; Jackson, SE (Elsevier, 2019)
Objectives: To investigate the effect of weight stigma in news media on (a) intentions to increase physical activity (PA), improve diet quality and lose weight, and (b) changes in PA, diet quality and body mass index (BMI) over one month, in (i) women of all weight categories and (ii) a subsample of women living with obesity.